Springweight of yearling bearcubs - Hertel, Anne G.; Bischof, Richard; Langvall, Ola; Mysterud, Atle; Kindberg, Jonas; Swenson, Jon E.; Zedrosser, Andreas (Dryad Digital Repository, 2017)
Spring weight of yearling offspring of monitored females, 2007-2016. Bears were darted from a helicopter and weighed in a sling suspended beneath a spring scale.